PHYSICAL AND CHEMICAL QUALITIES OF CORN WITH DIFFERENT MOISTURE LEVELS SUPPLEMENTED WITH MOLD INHIBITOR - Catootjie Lusje Nalle; Max A. J. Supit; Angga M. Akbar; Emiliana Langodai; Angriana So'o (BIOTROPIA, 2022)
Corn grain is used as the main energy source in poultry diet formulation. The quality of corn is easy to deteriorate during storage because of insect, fungal, and mycotoxin contamination. Efforts should be made to maintain the quality of corn during storage. The present study aimed to evaluate the physical and chemical quality of different moisture levels of corn supplemented by a mold inhibitor. A total of 750 kg of corn grain was used in the present study. A commercial mold inhibitor was used with a dose of 0.075%. The experimental design used was a 3 x 2 factorial complete randomized design. The first main factor was the different moisture levels (ML) of corn (≤10%, 10.0-10.9%; 11.0-11.9%), while the second main factor was mold inhibitor (MI, - or +). Thus, there were six treatment combinations, and each treatment comprised five replications. The results showed that ML, MI, and ML x MI interaction significantly (P<0.05 to 0.001) affected the percentage of grain damage and fungal grain but not (P>0.05) the moisture level of corn during 90 days of storage. Except for crude protein content, the ML did not affect (P>0.05) the proximate composition (PC) and gross energy (GE) content of corn. Except for dry matter (DM), the PC and GE content of corn were not affected (P>0.05) by MI. ML x MI interaction did not affect (P>0.05) the PC and GE content. The aflatoxin B1 (AFB1) content was similar (P>0.05) among all treatments. Except for histidine and lysine contents, the amino acid contents of corn were not affected by ML, MI, or ML x MI combination. In conclusion, the supplementation of MI in corn with different ML improved the physical quality, DM, ash, and GE content of corn grain during the storage; MI maintained the DM content but did not reduce the AFB1 content of corn. Except for histidine and lysine, the supplementation of MI in corn with different ML did not affect the amino acid content of corn.